Rotational cattle grazing improves understory vegetation biodiversity and structural complexity in oil palm plantations - Nobilly, Frisco; Sharifah Nur Atikah; Yahya, Muhammad Syafiq; Jusoh, Shokri; Cun, Grace S.; Norhisham, Ahmad Razi; Tohiran, Kamil Azmi; Raja Zulkifli; Badrul Azhar (John Wiley & Sons, 2021)
Herbicide overuse decimates understory vegetation, including those beneficial plants which may lead to a reduction of some production-related ecosystem services such as nutrient cycling, water regulation, natural pest control, and pollination. Such conventional weed management practices need to be replaced with environmentally friendly methods such as ecological grazing to make palm oil supply chain environmentally sustainable. Contrary to chemical weeding, livestock integration is believed to be a useful tool to control weeds without negative impact to human health and the environment. However, little is known about the influence of different livestock grazing practices on oil palm understory vegetation. Thus, the present study investigates the effects of weed management practices (i.e., rotational grazing, free-ranged grazing, and conventional weeding) on understory vegetation species richness, composition assemblages, and structural complexity. Based on plant surveys that were conducted on 360 sampling points, 120 understory vegetation species consisting of grasses, sedges, ferns, and legume covers were recorded. We found understory vegetation composition assemblages were different between treatments. Results revealed that the number of understory vegetation species, coverage, and height were significantly higher in rotational grazing compared with other practices. Given the major contribution of vegetation composition assemblages and structure on palm oil productions and biodiversity, oil palm growers should adopt rotational livestock grazing as a part of an integrated pest management strategy to control understory vegetation.